"My story of Malaysia and China" speak up short video contest - Ting, Hie-Ling (Corporate Communication Unit, UiTM Mukah Campus, 2025)
From November 1st to 31st December, the Confucius Institute, University of Malaya organized the “My Story of Malaysia and China” Speak Up Short Video Contest, which aimed to strengthen the friendship between both nations and inspire enthusiasm for Chinese language learning. This competition attracted numerous participants from various educational institutions. Students from Faculty of Business and Management, Universiti Teknologi MARA, Mukah campus took part in this event. They poured their hearts and efforts into creating short videos that vividly told their unique stories about the two countries, showcasing their deep insights into the rich cultures and friendly exchanges between Malaysia and China.